Interactive Systems: Bridging the Gaps Between Developers and Users - Grudin, Jonathan (IEEE Computer, 1991)
Today, user needs are recognized to be important in designing interactive computer systems, but as recently as 1980, they received little emphasis. In most major systems development companies, the basic organizational structures and development processes were defined in an earlier era, when the dialogue between computer systems and computer user did not have to be considered.